Ex-Dividend Date Anomaly : Evidence from Nordic Stock Exchanges 2005-2016 - Lepistö, Matti (fi=Turun yliopisto|en=University of Turku|, 2018)
Dividends and dividend policies of companies have been a field of study which has gained a wide interest in the finance research for a long time. Ex-dividend date is a specific date for a given company before the share must be bought if the investor wants to have the right for the dividend. The classical theories of finance suggest that the amount of the dividend distributed should not affect the valuation of the share, and the price drop on ex-dividend should be approximately the size of the paid dividend. Price drops not equaling the amount of the distributed dividend would generate abnormal returns. There are several studies that show abnormal returns around the ex-dividend date, which is considered to be anomalistic. The study aims to find out if the ex-dividend date anomaly exists in Nordic stock exchanges. This is done by using event study methodology. The sample of the study consists of shares from Finland, Sweden and Denmark. In addition, the study intends to find whether the size of the dividend has effect on price behavior around the ex-dividend date. There are several explanatory theories for ex-dividend date which all explain the anomaly by market imperfection or set of imperfections. The empirical results suggest that there are abnormal returns in Nordic stock exchanges around the ex-dividend date. This gives support for the existence of the ex-dividend date anomaly. The results show also that the size of the dividend yield has effect on the price behavior around the ex-dividend date.